Case Reports of Human Monkeypox Virus Infections, Uganda, 2024 - Nicholas Bbosa; Stella E. Nabirye; Hamidah S. Namagembe; Ronald Kiiza; Alfred Ssekagiri; Mary Munyagwa; Arafat Bwambale; Stephen Bagonza; Henry Kyobe Bosa; Robert Downing; Julius Lutwama; Pontiano Kaleebu; et al. (Emerging Infectious Diseases)
Mpox is a zoonotic disease caused by the monkeypox virus. We report on human mpox cases in Uganda identified by PCR and confirmed by deep sequencing. Phylogenetic analysis revealed clustering with other clade Ib sequences associated with recent outbreaks in the Democratic Republic of the Congo.